Comparing monovalent and combination hepatitis B vaccine outcomes in children delivered by mothers with chronic hepatitis B. (30th August 2018) - Lee, Le Y; Chan, Si M; Ong, Christina; M Aw, Marion; Wong, Franco; Saw, Sharon; Lee, Guan H; Thoon, Koh C; Phua, Kong B
Abstract : Aim: We compared the vaccine effectiveness of monovalent and combination hepatitis B vaccine regimens in infants born to chronic hepatitis B carrier mothers. Methods: An observational cohort of neonates was recruited over 78 months from two public hospital maternity units in Singapore. We enrolled term infants, born to chronic hepatitis B surface antigen‐positive mothers regardless of their hepatitis Be antigen status, who completed the hepatitis B virus (HBV) vaccination programme in Singapore. Infants born to mothers on antiviral therapy, or with concurrent hepatitis C or human immunodeficiency virus infection were excluded. All infants received hepatitis B immunoglobulin at birth. One group received three doses of monovalent hepatitis B vaccine (0, 1, 6 months) (regimen A). The other group received two doses of monovalent vaccine, followed by one dose combination vaccine DTaP‐IPV‐Hib‐HBV (0, 1, 6 months) (regimen B). Vaccine effectiveness was determined by immunoprophylaxis failure leading to HBV vertical transmission. Immunogenicity was assessed by hepatitis B surface antibody (anti‐HBs) levels at 9 months of age. Results: Total of 177 term neonates received regimen A and 115 received regimen B. Immunoprophylaxis failure rate was low, 2.3 and 2.6% ( P  = 1.00) in regimen A and B, respectively. Mean anti‐HBs titres were similar at 643 ± 374 and 561 ± 396 IU/L ( P  = 0.08) for regimen A and B, respectively. Conclusion: Hepatitis B vaccine regimens using monovalent or combination vaccine for the third dose showed similarly high vaccine effectiveness and low immunoprophylaxis failure rate in term infants born to chronic hepatitis B carrier mothers.